Corrosion behaviour of multiwall carbon nanotube/magnesium composites in 3.5% NaCl - Turhan, Can Metehan; Li, Qianqian; Jha, Himendra; Singer, Robert; Virtanen, Sannakaisa (Electrochimica Acta, 2011)
Corrosion behaviour of multiwall carbon nanotube (MWNT) modified pure magnesium (Mg) composites (MWNT/Mg) prepared by melt stirring technique was investigated by weight loss, H2 gas collection and pH measurements, as well as electrochemical methods such as open circuit potential (OCP) monitoring, polarisation curves and electrochemical impedance spectroscopy (EIS). Results show that the corrosion rate of MWNT/Mg composites is significantly higher than the corrosion rate of pure Mg. The corrosion rate of the composites also depends on the degree of dispersion of MWNTs during melt stirring process. The role of the MWNTs in increasing the corrosion rate clearly can be attributed to their high cathodic activity. Characterization of the corrosion product layers indicates that dispersion of MWNTs in the matrix leads to a more homogeneous coverage of the surface by corrosion products, and the lowest thickness of the corrosion product layer. The corrosion product layers in all cases provide poor protection of the surface. The corrosion rate of pure Mg as well as Mg/MWNT composites significantly increases during 1-week immersion; this effect is the strongest for the composite with dispersed nanotubes and can be attributed to the increased cathodic kinetics with time.